Evaluasi Kebugaran Jasmani Anggota Tarung Derajat Satlat Siginjai Berdasarkan Uji VO2MAX Via Website Topend Sports - Febriza, Nabil Afiqra; Hidayah, Krisvoniawati; Arisyi, Muhammad Fathan; Fauziyanti, Septiya; Yudiani, Walam; Widowati, Atri (MAN Insan Cendekia Jambi, 2025)
Physical fitness plays a pivotal role in supporting athletic performance, particularly in high-intensity sports such as Tarung Derajat, which demands a combination of strength, speed, and endurance. This study aimed to evaluate the aerobic capacity of Tarung Derajat athletes from Satlat Siginjai by estimating their VO₂MAX using the indirect method of the 20-meter Shuttle Run Test (Beep Test). To enhance accuracy and efficiency, VO₂MAX values were calculated using an online calculator provided by the Topend Sports website. The research employed a quantitative descriptive approach involving 15 active members who met the inclusion criteria. Results indicated that the majority of participants fell into the